The Role of Pensions in Poverty Reduction in Ghana - LARYEA MARGARET MOMO; CHARLES ANDOH; PATRICK ASUMING (African Journal of Governance and Development, 2019)
The study determines the extent to which pensions contribute to poverty reduction in Ghana. Using a logistic regression model, we determine the probability of a household being poor given pension income and other socio-demographic factors. The findings, based on the most recent (2012/2013) Ghana Living Standard Survey, round six data set, revealed that pensions in Ghana have no significant impact on poverty reduction for both absolute and extreme poverty levels.